The Effect of Fornication in Spreading the Sanctity of A Comparative Study Between Sharia and Positive Law - Abd , Obaid (Islamic Sciences Journal, 2023)
ABSTRACT It is revealed through my research by the theme (Adultery and its effect in spreading the sanctity), that the Islamic forbade adultery and considered it one of the major crimes and imposed the most severe penalties. If the adulterer is not married, the punishment is one hundred lashes ,but if he is married, male or female, his punishment is stoning to death. If the crime of adultery is committed with an incest, the majority of Muslim jurists unanimously agree that his punishment is stoning until death. However, lawfully the crime of adultery is not considered a crime unless the adultery committed by a man or a woman on the marital bed